PENGARUH PERSEPSI HARGA, KUALITAS PELAYANAN, DAN KUALITAS PRODUK DI RESTORAN HOKA-HOKA BENTO MALL GRAHA CIJANTUNG - Chastuti Kasanah; Salman Paludi (PT Naureen Digital Education, 2023)
Abstract is This study aims to examine the effect of perceived price, service quality, and product quality on customer satisfaction at Hoka-Hoka Bento Mall Graha Cijantung. This survey was conducted on customers who had purchased Hoka-Hoka Bento products at Hokben Mall Graha Cijantung during April-May 2023. In this study, a quantitative method was used. Primary data was collected through questionnaires which were distributed using the accidental sampling method. The number of respondents involved in this study were 100 respondents. The collected data is then carried out using several tests, namely validity tests and reliability tests. Data analysis involves the use of multiple linear regression analysis methods, correlation coefficients, determinations. This analysis will be carried out using SPSS software version 25. These findings indicate that perceptions of price, service quality, and product quality have a partial effect on customer satisfaction. Overall, the findings of this study show gradually that these three variables influence customer satisfaction